Using halogen⋯halogen interactions or C/N–H⋯Cl hydrogen bonding to direct crystal packing in tetrachlorophthalic acid with N-heterocyclic compounds1. Issue 14 (19th February 2015) - Hu, Yanjing; Li, Zhiqiang; Zhao, Yiran; Yang, Yu; Liu, Faqian; Wang, Lei
<x xml:space="preserve">Abstract</x> Hydrogen bonding patterns and halogen⋯halogen interactions, C/N–H⋯Cl hydrogen bonding in a series of multi-component molecular structures constructed by tetrachlorophthalic acid with N-heterocycles were discussed.